2016
DOI: 10.1097/prs.0000000000002080
|View full text |Cite
|
Sign up to set email alerts
|

Increased Osteoid Formation in BMP-2–Loaded Silk-Based Screws

Abstract: The BMP-2-loaded silk-based fixation device in this study exhibited characteristics comparable to the current nonloaded silk screws with regard to integration and biocompatibility. However, functionalization of silk screws with BMP-2 appeared to allow for more organized collagen and osteoid deposition after 3 and 6 months and may increase the potential of successful remodeling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 62 publications
(76 reference statements)
0
11
0
Order By: Relevance
“…Previously, we demonstrated the capacity to load silkbased orthopedic devices with the antimicrobial drug Ciprofloxacin, 2 the osteoinductive growth factor bone morphogenic protein 2 (BMP2), 1,2 as well as the BMP2's peptide P24. 2 The study demonstrated the capacity to load different bioactive molecules, as well as the capacity for these molecules to maintain functionality.…”
Section: Detection Of Surface-coated Mirnas In Silk Screwsmentioning
confidence: 99%
See 3 more Smart Citations
“…Previously, we demonstrated the capacity to load silkbased orthopedic devices with the antimicrobial drug Ciprofloxacin, 2 the osteoinductive growth factor bone morphogenic protein 2 (BMP2), 1,2 as well as the BMP2's peptide P24. 2 The study demonstrated the capacity to load different bioactive molecules, as well as the capacity for these molecules to maintain functionality.…”
Section: Detection Of Surface-coated Mirnas In Silk Screwsmentioning
confidence: 99%
“…O rthopedic silk medical devices, prepared from silkworm silk derived from Bombyx mori, represent new and promising candidates for bone repair and tissue regeneration due to their mechanical properties, low immunological responses, biodegradability, and ease of functionalization. [1][2][3][4][5][6] For bone fracture fixation, as well as guided tissue formation, successful engineered biomaterials must be biocompatible and resorbable, present an environment with appropriate cues for cell differentiation and deposition of new matrix, provide appropriate mechanical properties, and exhibit osteoconductivity. To this end, we recently developed a variety of chemical, structural, and biomechanical modifications of silk to improve function for bone tissue fracture repairs.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Bioengineered silk protein delivery vehicles are an appealing candidate for mediating BMP7 delivery to WAT, as silk is a readily available natural resource (such as from silkworm production), is non-immunogenic, and is able to be engineered into microspheres, hydrogels and other drug delivery systems that protect the ‘drug’ from degradation, but are able to be regulated to control drug release kinetics (( Guziewicz et al, 2011 ; Hines and Kaplan, 2011 ; Pritchard et al, 2013a ; Pritchard et al, 2013b ; Guziewicz et al, 2013 ; Coburn et al, 2015 ; Lovett et al, 2015 ; Kluge et al, 2016 ; Zhang et al, 2017 )). Silk-mediated delivery of BMP2 has already been optimized in vitro and in mouse models ( Diab et al, 2012 ; Shi et al, 2013 ; Zhang et al, 2014 ; Koolen et al, 2016 ; Shen et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%